Les banquets publics sous la République romaine : des banquets pour le populus ? - Christophe Badel (Astérion)
The public banquet category, which opposed convivium privatum and convivium publicum, existed in Roman society. Contrary to popular belief, the Latin term epulum did not always and, not only, refer to the public banquet, because the words convivium and cena could also be used. Originally, public banquets – ritual banquets or investiture banquets for priests and magistrates (cena aditialis) – concerned only priests and magistrates, sometimes senators (Epulum Iovis). These participants had the epulandi publice ius. In 217, the Saturnales banquet was opened to the populus but this case remained isolated in the ritual setting. On the other hand, from the beginning of the 2nd century, nobles made it a habit to offer banquets to the people at their family funerals, then in the 1st century, the imperatores did so first during the Tithe of Hercules and then during their triumphs. In these circumstances, the convivium publicum then became the epulum populi romani and the epulandi publice ius concerned the members of the populus, probably listed. Such an evolution shows that the presence of the populus was not consubstantial, under the Republic, at the public banquet. It also shows that the public character of a banquet was not determined by the status of the donor or the origin of the funds but by the status of representatives of the city of the beneficiaries (magistrates, senators or citizens), as well as by its location in a public place.